Who belongs? Co-creating an assessment to measure belonging in a community space - Monique Quinn; Sierra Roundtree; Lauren Porter; Kimberly Cutler; Kate Hanisian; Carley Riley (PLoS ONE, 2026)
It is inherent to human nature to want to belong, and a strong sense of belonging has been closely correlated with multiple metrics of wellbeing on an individual and community level. Ensuring improvement in sense of belonging requires accurate measurement of belonging within the community of interest, an effort that has previously been constrained to primarily education and employment spaces and often lacking community voice. In this paper, we describe a novel approach to survey development, wherein we combine community voice with existent validated survey tools to develop a measure of a construct – sense of belonging in this instance – within a timeframe that better fits community desired pace for progress and change. In partnership with the YMCA of Greater Cincinnati, we worked within a Community Based Participatory Research (CBPR) approach to measure sense of belonging using a combination of literature review, extraction and qualitative research methods. External member checking and a Cronbach alpha analysis illustrate success in measuring the construct of interest: sense of belonging within the context of YMCA membership.